A nuclear CobW/WW-domain factor represses the CO 2 -concentrating mechanism in the green alga Chlamydomonas reinhardtii - Daisuke Shimamura; Junko Yasuda; Yosuke Yamahara; Hirobumi Nakano; Shin-Ichiro Ozawa; Ryutaro Tokutsu; Ayumi Yamagami; Tomonao Matsushita; Yuichiro Takahashi; Takeshi Nakano; Hideya Fukuzawa; Takashi Yamano (Proceedings of the National Academy of Sciences, 2026)
Microalgae induce a CO 2 -concentrating mechanism (CCM) to maintain photosynthesis when CO 2 is limited. Because this system consumes a substantial portion of photosynthetically generated ATP, its suppression when CO 2 levels rise is critical for energy balance, yet the underlying mechanism remains unclear. Here, we identify a nuclear repressor of the CCM in the green alga Chlamydomonas reinhardtii . A pull-down screen for interacting partners of the master activator CCM1/CIA5 revealed an uncharacterized protein that tightly associates with CCM1. This protein, CCM1-binding protein 1 (CBP1), combines a CobW/CobW_C GTP-binding metallochaperone module with a WW-domain characteristic of protein–protein interactions. CBP1 colocalizes and interacts with CCM1 in the nucleus regardless of CO 2 conditions. Disruption of CBP1 does not affect growth or CCM induction under CO 2 limitation but derepresses 27 of 41 CCM1-dependent low-CO 2 inducible genes under high-CO 2 conditions. These include the periplasmic and intracellular carbonic anhydrases (CAH1 and LCIB) and inorganic carbon transporters/channels (LCIA, LCI1, BST1, and BST3). Consistently, cbp1 mutants accumulate CAH1 and LCIB proteins and exhibit 40% higher inorganic carbon affinity under high-CO 2 conditions; this phenotype is rescued by CBP1 complementation or by acetazolamide treatment. Crucially, cbp1 mutants exhibit significant growth delays under high-CO 2 conditions, especially when light is limiting, providing direct evidence that CBP1-mediated repression is essential for energy conservation. Thus, CBP1 prevents unnecessary CCM activity when CO 2 is abundant, acting upstream of both transporter/channel and carbonic anhydrase modules. Our findings suggest a regulatory mechanism potentially linking zinc-dependent protein chemistry to CCM gene repression, providing insights into energy-efficient CO 2 sensing in aquatic photosynthetic organisms.